ETIKA DAN INTEGRITAS ANGGOTA KEPOLISIAN - Tugimin Supriyadi; Aisyah Shinta Balkhis, Annisa Rahmawati, Gefira Adias Permata, Najla Alifah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Law enforcement and good public service play a crucial role in maintaining the order and security of a country. This research aims to investigate the relationship between ethics and integrity among police officers. By analyzing the concepts of ethics and integrity within the police force, this study seeks to understand the key role that moral values and integrity play in policing. Through a qualitative approach, this research attempts to elaborate on how ethics and integrity can be pragmatically integrated into policing practices to improve the quality of public service and strengthen the relationship between the police and the community